2005
DOI: 10.1111/j.1475-4754.2005.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization and Statistical Multivariate Analysis of Ancient Pottery From Messina, Catania, Lentini and Siracusa (Sicily)*

Abstract: This paper presents the chemical characterization of 79 fragments of Archaic and Hellenistic fine‐grained pottery from archaeological sites in Messina, Catania, Lentini and Siracusa (Sicily). The sherds were classified as ‘calcidian’, ‘banded’, ‘unvarnished’ and ‘black varnished’ pottery. The major and trace elements identified by X‐ray fluorescence (XRF) were statistically elaborated using the method proposed by J. Aitchinson in 1986 for the analysis of compositional data. From cluster analyses using element/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 8 publications
0
40
0
1
Order By: Relevance
“…On the other hand, since potters tend to process these raw materials, for instance by mixing different kinds of clay or mixing clays with crushed rocks, the composition of a ceramic sherd would also highlight the technological choices the potter made for the production of their pottery. In the case of elemental composition, the most widely used techniques are neutron activation analysis (NAA) and X-ray fluorescence (XRF) spectroscopy (Tsolakidou and Kilikoglou, 2002;Glascock et al, 2004;Barone et al, 2005;Padilla et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, since potters tend to process these raw materials, for instance by mixing different kinds of clay or mixing clays with crushed rocks, the composition of a ceramic sherd would also highlight the technological choices the potter made for the production of their pottery. In the case of elemental composition, the most widely used techniques are neutron activation analysis (NAA) and X-ray fluorescence (XRF) spectroscopy (Tsolakidou and Kilikoglou, 2002;Glascock et al, 2004;Barone et al, 2005;Padilla et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of a large number of kilns in Sicily and the presence of several clay formations suitable for ceramic manufacturing [2] suggests a prosperous production of potteries in ancient times. For these reasons, much research has been performed in recent years both on clays sediments [3][4][5] and kilns materials [6][7][8][9][10] with the aim of highlighting the features of Sicilian productions.…”
Section: Introductionmentioning
confidence: 99%
“…Hyblean two representative samples from S. Agata al Carcere also ascribes them to the Etnean area, providing new data to the hypothesis of a production persistence in Catania, previously recognised for the Greek period by Barone et al (2005). As regards the sherds from Messina, most of them consists of Greek-Italic amphorae (together with a small number of Richborough 527 and ''orlo a quarto di cerchio'' samples), whose productive centres are still unknown at present.…”
Section: Mt Etnamentioning
confidence: 89%
“…Many papers on the archaeometric study of ancient pottery from this area can be found in the literature (Agodi et al, 1998(Agodi et al, , 2000Barone et al, 2005;Barra Bagnasco et al, 2001;Barrese et al, 2003;Eramo et al, 2004;Iliopoulos et al, 2002;Laviano and Muntoni, 2003;Levi, 1999;Lombardo et al, 2000;Montana et al, 2003). However, attributions of provenance after petro-chemical characterisation are in many cases uncertain, due to: (a) the frequent lack of literature data on clayey sediments outcropping near the potential productive sites; (b) the use of raw materials which are, in some cases, compositionally similar on a large geographic scale (e.g.…”
Section: Introductionmentioning
confidence: 98%